Characterization of GmMATE13 in its contribution of citrate efflux and aluminum resistance in soybeans - Wang, Zhengbiao; Liu, Yuanqi; Cui, Wenmo; Gong, Li; He, Ying; Zhang, Qingxiu; Meng, Xiangxiang; Yang, Zhenming; You, Jiangfeng (Frontiers in Plant Science, 2022)
Citrate exudation mediated by citrate transporter of MATE protein family is critical for resisting aluminum (Al) toxicity in soybean. However, the expression patterns of citrate transporter genes differred under Al stress. Thus, exploring the responsive pattern of GmMATEs in response to Al stress is of great importance to understand Al resistance mechanism in soybean. In the present study, the phylogenetic analysis, the transcriptional expressed pattern and the function of GmMATE13 were investigated. The results showed that soybean GmMATE13 is highly homologous to known citrate transporter proteins from other plants. Under Al exposure, the transcript abundance of GmMATE13 was increased during 24 h Al treatment period. The expression of GmMATE13 is specifically induced by Al exposure, but not by the status of Fe, Cu, Cd or La. Moreover, it was also highly increased when the soybean seedlings were grown on acidic soil with high Al content. Subcellular localization showed that GmMATE13 was localized on the plasma membrane when it were transiently expressed in Arabidopsis protoplasts. Investigation of tissue localization of GmMATE13 expression by investigating GUS activity staining under the control of GmMATE13 promoter showed that it was mainly expressed in central cylinder in the root tips of the soybean under Al-free condition, while extended to cortical and epidermis cells under Al stress. Finally, overexpressing GmMATE13 in soybean hairy roots enhanced the Al resistance by increasing citrate efflux. Collectively, we conclude that GmMATE13 is a promising candidate to improve the resistance of soybean to Al toxicity in acidic soil.